A facile and efficient synthesis approach of salidroside esters by whole-cell biocatalysts in organic solvents - Yang, Rongling; Wang, Yu; Zhao, Xiangjie; Tong, Zheng; Zhu, Qianlin; He, Xiaoxi; Wang, Zhaoyu; Luo, Hongzhen; Fang, Fang (Frontiers in Bioengineering and Biotechnology, 2022)
Salidroside, the main bioactive compound isolated from the plant source of Rhodiola rosea L, possesses broad-spectrum pharmacological activities, but suffers from the low cell membranes permeability and alimentary absorption due to its high polarity. Therefore, a whole-cell catalytic strategy for the synthesis of salidroside esters was explored to improve its lipophilicity. The results showed that Aspergillus oryzae demonstrated the highest biocatalytic activity among the microbial strains tested. For the synthesis of salidroside caprylate, the optimum conditions of reaction medium, Aspergillus oryzae amount, molar ratio of vinyl caprylate to salidroside and reaction temperature were acetone, 30 mg/mL, 10 and 40 °C, respectively. Under these conditions, the initial reaction rate was 15.36 mM/h, and substrate conversion and regioselectivity all reached 99%. Moreover, the results indicated that although various 6′-monoesters derivatives of salidroside were exclusively obtained with excellent conversions (96%-99%), the reaction rate varied greatly with different chain-length acyl donors. This study details an efficient and cost-effective biocatalytic approach for the synthesis of salidroside esters by using Aspergillus oryzae as a catalyst for the first time. Considering the whole cell catalytic efficiency and operational stability, this strategy may provide a new opportunity to develop green industrial processes production for ester derivatives of salidroside and its analogues.